2021
DOI: 10.1039/d1cy00855b
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric azidohydroxylation of styrene derivatives mediated by a biomimetic styrene monooxygenase enzymatic cascade

Abstract: Enantioenriched azido alcohols are precursors for valuable chiral aziridines and 1,2-amino alcohols, however their chiral substituted analogues are difficult to access. We established a cascade for the asymmetric azidohydroxylation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 65 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…Moreover, regioisomers 3a and especially 6a were formed with high regioselectivity in the HHDHcatalysed step (Table 2). Thus, our StyAB + HHDH cascade for the synthesis of aliphatic 2,3azidoalcohols compares favourably, in terms of regioselectivity, with the recently published cascade for the synthesis of aryl aliphatic azidoalcohols [12]. Overall, the poor organic solvent tolerance of the used HHDHs, HheE and HheE5, turned out to be a main limiting factor regarding product yield in both cascades, but also enantioselectivity in cascade 1.…”
Section: Cascade Runsmentioning
confidence: 58%
See 4 more Smart Citations
“…Moreover, regioisomers 3a and especially 6a were formed with high regioselectivity in the HHDHcatalysed step (Table 2). Thus, our StyAB + HHDH cascade for the synthesis of aliphatic 2,3azidoalcohols compares favourably, in terms of regioselectivity, with the recently published cascade for the synthesis of aryl aliphatic azidoalcohols [12]. Overall, the poor organic solvent tolerance of the used HHDHs, HheE and HheE5, turned out to be a main limiting factor regarding product yield in both cascades, but also enantioselectivity in cascade 1.…”
Section: Cascade Runsmentioning
confidence: 58%
“…The aim of this work was to expand the range of accessible enantiopure azidoalcohols through a combination of alkene epoxidation and subsequent epoxide azidolysis, as recently reported for the generation of styrene-based azidoalcohols [12]. Here, we have demonstrated that this strategy can be extended to linear non-terminal alkene substrates, giving access to a broader range of possible azidoalcohol products.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations